Housing and Health: Here We Go Again - Lorenzo Capasso (MDPI AG, 2021)
Housing is one of the major determinants of human health and the current COVID-19 pandemic has highlighted its relevance. The authors summarize the main issues, including dimensional standards, indoor air quality, safety, accessibility, neighborhoods, and area characteristics. The authors propose an operating scheme in order to implement actions to improve residential wellbeing on a local, national, and international level.